Stress-Responsive Periplasmic Chaperones in Bacteria - Kim, Hyunhee; Wu, Kevin; Lee, Changhan (Frontiers in Molecular Biosciences, 2021)
Periplasmic proteins are involved in a wide range of bacterial functions, including motility, biofilm formation, sensing environmental cues, and small-molecule transport. In addition, a wide range of outer membrane proteins and proteins that are secreted into the media must travel through the periplasm to reach their final destinations. Since the porous outer membrane allows for the free diffusion of small molecules, periplasmic proteins and those that travel through this compartment are more vulnerable to external environmental changes, including those that result in protein unfolding, than cytoplasmic proteins are. To enable bacterial survival under various stress conditions, a robust protein quality control system is required in the periplasm. In this review, we focus on several periplasmic chaperones that are stress responsive, including Spy, which responds to envelope-stress, DegP, which responds to temperature to modulate chaperone/protease activity, HdeA and HdeB, which respond to acid stress, and UgpB, which functions as a bile-responsive chaperone.